Azomethine Ylides from Nitrones: Using Catalytic nBuLi for the Totally Stereoselective Synthesis of trans‐2‐Alkyl‐3‐oxazolines. Issue 33 (30th June 2016) - Juste‐Navarro, Veronica; Delso, Ignacio; Tejero, Tomás; Merino, Pedro
Abstract: The cycloaddition of azomethine ylide N ‐oxides (nitrone ylides) with aldehydes provides 3‐oxazolines in a completely stereoselective manner in the presence of a catalytic amount of n ‐butyllithium. The process involves an initial nucleophilic attack on the aldehyde, followed by intramolecular oxygen addition to the nitrone moiety and lithium‐assisted elimination of water, regenerating the catalytic species. Various Li‐based catalytic systems are possible and the in situ generated water is required for continuing the catalytic cycle. The best results are observed with 20 mol % of n ‐butyllithium, whereas the use of stoichiometric amounts inhibit the rate of catalysis. Experimental, spectroscopic, and computational mechanistic studies have provided evidence of lithium‐ion catalysis and rationalized several competing catalytic pathways Abstract : Water and n BuLi together at last : The reaction between nitrone ylides and aldehydes in the presence of catalytic amounts of n BuLi provides 3‐oxazolines with complete trans ‐selectivity. DFT calculations rationalize the role of in situ generated water for the progress of the catalytic cycle.